2008
DOI: 10.1179/joc.2008.20.2.263
|View full text |Cite
|
Sign up to set email alerts
|

O6- Methylguanine-DNA-Methyltransferase in Recurring Anaplastic Ependymomas: PCR and Immunohistochemistry

Abstract: Ependymomas are the third most common brain tumor in children. The post surgical management is controversial. There are no convincing data on an effective role for chemotherapy. O(6)-Methylguanine-DNA-Methyltransferase (MGMT) is a DNA repair protein considered to be a chemosensitivity predictor. Hypermethylation of the MGMT gene promoter is an important cause of MGMT inactivation. We evaluated the MGMT gene promoter methylation and the immunohistochemical MGMT protein expression in 12 recurrent anaplastic epen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…The report by Chamberlain and Johnston [48] showed minimal activity, whereas the ongoing study at the University of Torino has shown promising early results [50]. However, recent reports suggest that a large percentage of ependymomas express high levels of MGMT, an enzyme that confers resistance to alkylating agents such as temozolomide [32]. This suggests that alternative schedules, such as more prolonged, dosedense schedules, may have improved efficacy because these have been shown to deplete MGMT in peripheral blood lymphocytes.…”
Section: Intracranial Tumorsmentioning
confidence: 93%
See 1 more Smart Citation
“…The report by Chamberlain and Johnston [48] showed minimal activity, whereas the ongoing study at the University of Torino has shown promising early results [50]. However, recent reports suggest that a large percentage of ependymomas express high levels of MGMT, an enzyme that confers resistance to alkylating agents such as temozolomide [32]. This suggests that alternative schedules, such as more prolonged, dosedense schedules, may have improved efficacy because these have been shown to deplete MGMT in peripheral blood lymphocytes.…”
Section: Intracranial Tumorsmentioning
confidence: 93%
“…Similarly, overexpression of the α v β 3 integrin was found in a high percentage of ependymomas, and there now are specific agents targeting this integrin [21]. The finding that most ependymomas overexpress MGMT may provide insight into the overall poor response of ependymoma to conventional cytotoxic chemotherapy, as this enzyme is a major mechanism of resistance to alkylating agents [32]. Therefore, strategies to modulate MGMT activity may have benefit in ependymomas.…”
Section: Implications For Prognosis and Treatmentmentioning
confidence: 93%
“…Pediatric glioblastoma stem cells display resistance to radiation because of preferential activation of the DNA damage checkpoint (163,164), whereas xenograft models have attributed varying radiation resistance between ependymomas to possible inherent differences in p53 mediated growth arrest (160). Overexpression of the DNA repair protein and chemosensitivity marker MGMT in a small series of recurrent pediatric ependymomas suggests a possible implication in anaplastic ependymoma chemoresistance (165). Additionally, distinct populations of forebrain neural stem and progenitor cells can be isolated on the basis of their ability to efflux the fluorescent dye Hoechst 33342, indicative of high expression of ATP-binding cassette (ABC) drug transporters (166,167).…”
Section: Therapeutic Implications For Researchmentioning
confidence: 99%
“…Nevertheless, it has been demonstrated that the histological tumor grade is also a predictor of the clinical behavior. Actually, WHO III anaplastic ependymomas show an unfavorable outcome [3].…”
Section: Log Rqmentioning
confidence: 99%
“…Eight (50%) were from men and 8 (50%) were from women. The average age at the time of the first surgery at our institution was 7 years (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] …”
Section: Patientsmentioning
confidence: 99%